2019
DOI: 10.4314/ahs.v19i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics prescription pattern and determinants of utilization in the national health insurance scheme at a Tertiary Hospital in Nigeria

Abstract: Background: Subsidizing the cost of medicines through insurance schemes increases consumption of medicines and may contribute to irrational use of antibiotics. Objectives: To describe the systemic antibiotics prescriptions patterns and analyze the determinants of their utilization in the National Health insurance Scheme (NHIS).Methods: Established WHO guideline was followed to conduct this cross-sectional retrospective study at University of Nigeria Teaching Hospital, Nigeria. Data were collected from randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 14 publications
3
19
2
Order By: Relevance
“…This may be attributed to their widespread use and frequent prescription by health care providers. Metronidazole, Ciprofloxacin and Amoxycillin are the commonly prescribed antibiotics in Nigeria [56,57]. Ciprofloxacin has been detected at lower concentration in Ugandan Lake Victoria at 91% frequency [23].…”
Section: Antibioticsmentioning
confidence: 99%
“…This may be attributed to their widespread use and frequent prescription by health care providers. Metronidazole, Ciprofloxacin and Amoxycillin are the commonly prescribed antibiotics in Nigeria [56,57]. Ciprofloxacin has been detected at lower concentration in Ugandan Lake Victoria at 91% frequency [23].…”
Section: Antibioticsmentioning
confidence: 99%
“…This finding was corroborated by Ngwaiet al(2020) who found that antibiotic encounter was higher in the 10 years and below age group than among older population. However, Okoro, Nmeka and Erah (2019) finding showed that patients less than 5 years had higher antibiotic encounter than older population. There is no gender disparity in the use of antibiotics as differences in antibiotics encounter were not statistically significant (X 2 = 0.530, df= 1, p>0.05).…”
Section: Discussionmentioning
confidence: 88%
“…The odds of having antibiotics in the prescription reduces by 3% for every unit increase in age (OR = 0.97; 95% CI: 0.97, 0.98). In Nasarawa state, North-Central Nigeria, a descriptive retrospective cross-sectional study involving 2800 cases between 2008 and 2018 showed that antibiotics prescription was highest in the 10 years and below age category (67%) and lowest for those greater than 50 years (Ngwaiet al, 2020).However, a crosssectional study of 802 National Health Insurance Scheme (NHIS) prescriptions from University of Nigeria Teaching Hospital showed that patients less than 5years has highest risks of antibiotic exposure (Okoro, Nmeka, &Erah, 2019).…”
Section: Antibiotics Use and Agementioning
confidence: 99%
See 1 more Smart Citation
“…The papers on bacterial infections include antibiotic prescriptions, self-medication, diagnosis and neonatal sepsis. Hence from a tertiary hospital in Nigeria, we have a paper on antibiotics prescription and determinants of utilization 7 , while from Indonesia we have a report on self-medication profile for diarrhea with traditional medication 8 . The paper on the role of C-reactive protein in the diagnosis of meningitis 9 and the two papers on neonatal sepsis 10,11 shine some light on infections in children.…”
mentioning
confidence: 99%